Speech, Language, and Oromotor Skills in Patients With Polymicrogyria. (6th April 2021) - Braden, Ruth O.; Boyce, Jessica O.; Stutterd, Chloe A.; Pope, Kate; Goel, Himanshu; Leventer, Richard J.; Scheffer, Ingrid E.; Morgan, Angela T.
Abstract : Objective: To determine whether specific speech, language, and oromotor profiles are associated with different patterns of polymicrogyria, we assessed 52 patients with polymicrogyria using a battery of standardized tests and correlated findings with topography and severity of polymicrogyria. Methods: Patients were identified via clinical research databases and invited to participate, irrespective of cognitive and verbal language abilities. We conducted standardized assessments of speech, oromotor structure and function, language, and nonverbal IQ. Data were analyzed according to normative assessment data and descriptive statistics. We conducted a correlation analysis between topographic pattern and speech and language findings. Results: Fifty-two patients (33 male, 63%) were studied at an average age of 12.7 years (range 2.5–36 years). All patients had dysarthria, which ranged from mild impairment to anarthria. Developmental speech errors (articulation and phonology), oral motor structure and function deficits, and language disorder were frequent. A total of 23/29 (79%) had cognitive abilities in the low average to extremely low range. In the perisylvian polymicrogyria group (36/52), speech, everyday language, and oral motor impairments were more severe, compared to generalized (1 patient), frontal (3), polymicrogyria with periventricular nodular heterotopia (3), parasagittal parieto-occipital (1), mesial occipital (1), and other (7) patterns. Conclusions: Dysarthria is a core feature of polymicrogyria, often accompanied by receptive and expressive language impairments. These features are associated with all polymicrogyria distribution patterns and more severe in individuals with bilateral polymicrogyria, particularly in the perisylvian region.